Morphodynamics Study Of Coastline Region Using Smoothed Particle Hydrodynamics And Particle Image Velocimetry - Azman, Muhammad Aqil (2020)
Scour is the one of phenomena that occurs at coastal area which can cause catastrophic failure to structure near to the coastal area. The study of the scour in the coastal area is important in order to overcome the erosion occur near to coastal area. There is limited study which simulates liquid-sediment at coastal area. Most of researcher using 2-dimensional (2D) problem to solve liquid-sediment problem which will over simplify and reduce the complexity of the topography of coastal area. Consequently, this thesis simulates a 3D two-phase liquid-sediment numerical model by using particle based Smooth Particle Hydrodynamics (SPH) for application at coastal area. Initially, a preliminary study has been tested before application to real case. The SPH code is constructed based on formulation from Monaghan that is modified according to the desired model to be solved. The code is then computed by using single Graphic Processing Unit (GPU), Nvidia Quadro P4000 with 14 cores multiprocessors. The effect of scouring is investigated in this research through the formulation of sediment transport based on Herschel-Bulkley-Papanastasiou (HBP) model. An early model that used sine wave with varying frequencies are applied to the boundary to create sea wave effect that will then cause either sediment erosion or accretion at the coastline. The preliminary study of liquid-sediment interactions is computed numerically using SPH simulation which is then validated using PIV experimental data. The comparisons between SPH simulation and PIV experimental showed good agreement in the maximum velocity magnitude and contours with average percentage difference of 5%. Moreover, the correlation between two dimensionless numbers which are Iribarren and froude number have also been calculated by manipulating frequencies of wave and slope angles to determine the type of wave breaker. The research area was chosen near to Tenaga Nasional Berhad (TNB) Tuanku Jaafar power station to analyse the impact of sea wave to sediment transport. Based on real case study, the selected regions were analysed in order to reduce the complexity of the studies and directly captured the sediment transport. Based on the findings, region C experienced high sediment transport for constant wave study as compared to region A and B. The accretion at region C is 904.01 kg at 90 s while the mass erosion is 906.24 kg at 91 s. Compared to region B, the mass accretion is 902.24 kg at 90 s while the mass erosion is 903.24 kg at 91 s. Additionally, region A accreted a mass of 788.51 kg at a time of 24 s while eroding with a mass of 790.01 kg at a time of 23 s. The results for region A, B and C have been forecasted for the period of 10 years by using Fourier fitting curve with 8th order to observe the sediment transport trend. The prediction found that region C also experienced highest sediment transport with accretion mass of 7343.54 kg in 1.37 year for constant wave study and 876.44 kg at year 10 for low tide study.